Discovery of Novel and Potent Stearoyl Coenzyme A Desaturase 1 (SCD1) Inhibitors as Anticancer Agents. Issue 14 (15th July 2017) - Imamura, Keisuke; Tomita, Naoki; Kawakita, Youichi; Ito, Yoshiteru; Ono, Kouji; Nii, Noriyuki; Miyazaki, Tohru; Yonemori, Kazuko; Tawada, Michiko; Sumi, Hiroyuki; Satoh, Yoshihiko; Yamamoto, Yukiko; et al.
Graphical abstract: Abstract: A lead compoundA was identified previously as an stearoyl coenzyme A desaturase (SCD) inhibitor during research on potential treatments for obesity. This compound showed high SCD1 binding affinity, but a poor pharmacokinetic (PK) profile and limited chemical accessibility, making it suboptimal for use in anticancer research. To identify potent SCD1 inhibitors with more promising PK profiles, we newly designed a series of 'non-spiro' 4, 4-disubstituted piperidine derivatives based on molecular modeling studies. As a result, we discovered compound1a, which retained moderate SCD1 binding affinity. Optimization around1a was accelerated by analyzing Hansch–Fujita and Hammett constants to obtain 4-phenyl-4-(trifluoromethyl)piperidine derivative1n . Fine-tuning of the azole moiety of1n led to compound1o (T-3764518 ), which retained nanomolar affinity and exhibited an excellent PK profile. Reflecting the good potency and PK profile, orally administrated compound1o showed significant pharmacodynamic (PD) marker reduction (at 0.3 mg/kg, bid) in HCT116 mouse xenograft model and tumor growth suppression (at 1 mg/kg, bid) in 786-O mouse xenograft model. In conclusion, we identified a new series of SCD1 inhibitors, represented by compound1o, which represents a promising new chemical tool suitable for the study of SCD1 biology as well as the potential development of novel anticancer therapies.